FOSTERING TOLERANCE AMONG STUDENTS IN THE PROCESS OF LEARNING A FOREIGN LANGUAGE - Gaparova G. I. (Vestnik Issyk-Kulʹskogo universiteta)
This article discusses the education of tolerance among students in the process of learning a foreign language. The entry of mankind into the phase of transition from an industrial society to an information one dramatically increases the role of the spiritual factor, which includes science, education and culture. Also, an important aspect of the educational process is the education of cultural tolerance among students in the context of globalization and diversity. The article examines the role of learning a foreign language not only in the development of anguage skills, but also in a deeper study of the culture, traditions and customs of other peoples. Methods that promote empathy and democracy towards others, including interactive activities, intercultural exchange and research projects, will be discussed. Successful practices included in the education reform are being applied. As a result, recommendations will be given on education, implementation and respect for tolerance in the learning process. The integration of cultural aspects into the educational process ensures that students behave in various public places and treat society with respect, while remaining cultured and tolerant in life in a globalized society.